Effectiveness of BCG vaccination against Mycobacterium tuberculosis infection in adults: a cross-sectional analysis of a UK-based cohort - Katelaris,AL; Jackson,C; Southern,J; Gupta,RK; Drobniewski,F; Lalvani,A; Lipman,M; Mangtani,P; Abubakar,I (The Journal of Infectious Diseases, 2020)
BackgroundBCG appears to reduce acquisition of Mycobacterium tuberculosis (Mtb) infection in children, measured using interferon-gamma release assays (IGRAs). We explored whether BCG vaccination continues to be associated with decreased prevalence of Mtb infection in adults.MethodsWe conducted a cross-sectional analysis of data from adult contacts of tuberculosis cases participating in a UK cohort study. Vaccine effectiveness (VE) of BCG, ascertained based on presence of a scar or vaccination history, against latent tuberculosis infection (LTBI), measured via IGRA, was assessed using multivariable logistic regression. The effects of age at BCG and time since vaccination were also explored.ResultsOf 3453 recent tuberculosis contacts, 27.5% had LTBI. There was strong evidence of an association between BCG and LTBI (aOR=0.70, 95% CI 0.56-0.87, p=0.0017) yielding a VE of 30%. VE declined with time since vaccination, but there was evidence that LTBI prevalence was lower amongst vaccinated individuals even >20 years after vaccination, compared with non-vaccinated participants.ConclusionBCG is associated with lower prevalence of LTBI in adult contacts of tuberculosis. These results contribute to growing evidence that suggests BCG may protect against Mtb infection as well as disease. This has implications for immunisation programmes, vaccine development and tuberculosis control efforts worldwide.